An Environmental Scan for Early Mobilization Practices in U.S. ICUs - Bakhru, Rita N; Wiebe, Douglas J; McWilliams, David J; Spuhler, Vicki J; Schweickert, William D (Critical care medicine, 2015)
Early mobilization improves patient outcomes. However, diffusion of this intervention into standard ICU practice is unknown. Dissemination and implementation efforts may be guided by an environmental scan to detail readiness for early mobilization, current practice, and barriers to early mobilization. A telephone survey. U.S. ICUs. Five hundred randomly selected U.S. ICUs stratified by regional hospital density and hospital size. None. We surveyed 687 ICUs for a 73% response rate (500 ICUs); 99% of respondents were nursing leadership. Fifty-one percent of hospitals reported an academic affiliation. Surveyed ICUs were most often mixed medical/surgical (58%) or medical (22%) with a median of 16 beds (12-24). Thirty-four percent reported presence of a dedicated physical and/or occupational therapy team for the ICU. Overall, 45% of ICUs reported early mobilization practice; two thirds of ICUs with early mobilization practice reported using a written early mobilization protocol. In ICUs with early mobilization practice, 52% began the intervention at admission and 74% enacted early mobilization for both ventilated and nonventilated patients. Early mobilization was provided a median of 6 days per week, twice daily. Factors independently associated with early mobilization protocols include dedicated physical/occupational therapy (odds ratio, 3.34; 95% CI, 2.13-5.22; p<0.01), American Hospital Association region 2 (odds ratio, 3.33; 95% CI, 1.04-10.64; p=0.04), written sedation protocol (odds ratio, 2.36; 95% CI, 1.25-4.45; p<0.01), daily multidisciplinary rounds (odds ratio, 2.31; 95% CI, 1.29-4.15; p<0.01), and written daily goals for patients (odds ratio, 2.17; 95% CI, 1.02-4.64; p=0.04). Commonly cited barriers included equipment, staffing, patient and caregiver safety, and competing priorities. In ICUs without early mobilization adoption, 78% have considered implementation but cite barriers including competing priorities and need for further planning. Diffusion regarding benefits of early mobilization has occurred, but adoption into practice is lagging. Mandates for multidisciplinary rounds and formal sedation protocols may be necessary strategies to increase the likelihood of successful early mobilization implementation. Methods to accurately assess and compare institutional performance via practice audit are needed.